Indonesia ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KSPPS MELATI WONOSOBO (STUDI KASUS PADA ANGGOTA PROGRAM JEMPUT BOLA) - Firda Hidayatus (At-Tauzi : Jurnal Ekonomi Islam, 2024)
The purpose of this study is to analyze the effect of service quality on member satisfaction in the outreach program at the KSPPS Melati, Sapuran Branch. This research is quantitative with an associative approach. Data collection methods used questionnaires, observations, and interviews. The sample size was determined using a purposive sampling technique, which involves drawing sample members from the population using specific criteria. The results show that service quality (X) significantly influences member satisfaction (Y) at the KSPPS Melati, Sapuran Branch, Wonosobo. The regression value obtained is Y = 0.945 + 0.560X. The coefficient of determination indicates that member satisfaction (Y) is 0.910, or 91%, explained by the independent variable, namely service quality. The remaining 9% is influenced by other factors.